Bank Funding Strategies The Use of Bonds and the Bail-in Effect - Crespi, Fabrizio (Palgrave Macmillan Studies in Banking and Financial Institutions,, 2018)
This book illustrates the importance of bonds as a funding tool available to banks. After providing the reader with an overview of the funding strategies adopted during the last ten years by European banks, the book offers a deep focus on the Italian banking industry. Notably, the authors illustrate how bonds have been a primary funding choice for Italian banks, as well as a preponderant asset in Italian households' portfolios. Furthermore, they highlight the consequences of the adoption of the Bank Recovery and Resolution Directive (BRRD) on the yields offered by bonds of Italian banks. Finally, they conclude the volume with the illustration of very recent case studies about the application of the BRRD to some problematic banks in Italy and the related side effects generated to bank bondholders. All the analyses presented in the book are supported by the use of quantitative data.